International Flows to Latin America--Rocking the Boat? LAC Semiannual Report, April 2014 - de la Torre, Augusto; Beylis, Guillermo; de Piniés, Jaime (Washington, DC: World Bank, 2014)
As usual in this series, Chapter 1 reviews the configuration of global risks and assesses the outstanding short term opportunities and challenges facing the LAC region. A special focus is placed this time around on the difference between exposure and vulnerability to exogenous shocks, with the latter assessed by adjusting exposure for a country’s shock absorption policy capacity. Given the global context and associated concerns with capital flow volatility, in Chapter 2 we take a look at the comparatively more stable components of international flows: FDI and Remittances. The cyclicality and volatility, as well as the joint determinants of FDI and Remittances are reviewed.